2015
DOI: 10.1590/s0102-865020150050000002
|View full text |Cite
|
Sign up to set email alerts
|

Study of renal and hepatic toxicity in rats supplemented with creatine

Abstract: PURPOSE:To evaluate the renal and hepatic function, through biochemical analysis after 14 days of creatine supplementation in physically inactive rats. METHODS:Twenty four male, adult, Wistar rats were used which were kept in individual metabolic cages and were distributed into four groups, and received the following treatments by gavage:1) Control: distilled water; 2)Creatine 0.5g/Kg/day; 3) Creatine 1g/Kg/ day; 4) Creatine 2g/Kg/day. Their urinary outputs as well as food and water intake were daily measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
3
0
4
Order By: Relevance
“…For example, Ferreira and associates [260] reported that creatine feeding (2 g/kg/d for 10 weeks equivalent to 140 g/kg/d in a 70 kg person) had no effects on glomerular filtration rate and renal plasma flow in Wistar rats. Likewise, Baracho and colleagues [261] reported that Wistar rats fed 0, 0.5, 1, or 2 g/kg/d of creatine did not result in renal and/or hepatic toxicity. Poortmans and coworkers reported that ingesting 20 g/day of creatine for 5 days [243], and up to 10 g/day from 10 months to 5 years [257] had no effect on creatine clearance, glomerular filtration rate, tubular resorption, or glomerular membrane permeability compared to controls.…”
Section: Safetymentioning
confidence: 99%
“…For example, Ferreira and associates [260] reported that creatine feeding (2 g/kg/d for 10 weeks equivalent to 140 g/kg/d in a 70 kg person) had no effects on glomerular filtration rate and renal plasma flow in Wistar rats. Likewise, Baracho and colleagues [261] reported that Wistar rats fed 0, 0.5, 1, or 2 g/kg/d of creatine did not result in renal and/or hepatic toxicity. Poortmans and coworkers reported that ingesting 20 g/day of creatine for 5 days [243], and up to 10 g/day from 10 months to 5 years [257] had no effect on creatine clearance, glomerular filtration rate, tubular resorption, or glomerular membrane permeability compared to controls.…”
Section: Safetymentioning
confidence: 99%
“…O mecanismo de ação da creatina baseia-se no efeito de induzir a melhoria do metabolismo energético muscular, em que a creatina fosforilada é capaz de ressintetizar o ATP a partir do difosfato de adenosina, aumentando assim a sua deposição 6-8 vezes (BARACHO et al, 2015) Neste caso, observou-se que os níveis fisiológicos de creatina são benéficos para o corpo. No entanto, devido ao seu amplo uso como suplemento nutricional, é necessário avaliar cuidadosamente a possível toxicidade deste suplemento no metabolismo e na morfologia hepática, bem como na função renal, pois seus efeitos toxicológicos ainda são desconhecidos (BARACHO et al, 2015).…”
Section: Resultados E Discussõesunclassified
“…Outro efeito benéfico da suplementação de creatina é o aumento do tamanho da fibra muscular, bem como da massa corporal magra devido ao aumento da síntese de proteínas e diminuição do catabolismo. Finalmente, a creatina previne o dano tecidual, pois promove os mecanismos de estabilização da membrana celular e a manutenção do ATP (BARACHO et al, 2015).…”
Section: Resultados E Discussõesunclassified
“…34 And while toxicological data on creatine are limited, Baracho et al performed a 14-day study in 24 male rats and found no significant changes in liver or kidney function tests or urinalysis after oral administration of 0, 0.5, 1, or 2 g/kg bw/d of micronized creatine. 35 Creatine use in dietary supplements usually includes a loading dose of 20 to 30 g divided into 4 equal doses for 5 to 7 days followed by a 1 to 10 g/d maintenance dose, although some daily dose recommendations go as high as 20 to 30 g. 4,[36][37][38] In a recent review, Barcelos et al discussed the conflicting reports on creatine use concluding that creatine supplementation induces no real modification in liver metabolism in humans, while side effects of liver toxicity or renal toxicity from creatine supplementation are regarded as inconclusive. 36 Additionally, studies have reported mixed results of creatine's effect on creatinine (CREA) excretion in humans with some studies showing an increase [39][40][41][42] and others showing no increase.…”
Section: Discussionmentioning
confidence: 99%
“…34 And while toxicological data on creatine are limited, Baracho et al performed a 14-day study in 24 male rats and found no significant changes in liver or kidney function tests or urinalysis after oral administration of 0, 0.5, 1, or 2 g/kg bw/d of micronized creatine. 35…”
Section: Discussionmentioning
confidence: 99%